2013
DOI: 10.1088/1748-0221/8/02/p02006
|View full text |Cite
|
Sign up to set email alerts
|

A combined ultrasonic flow meter and binary vapour mixture analyzer for the ATLAS silicon tracker

Abstract: An upgrade to the ATLAS silicon tracker cooling control system may require a change from C 3 F 8 (octafluoro-propane) evaporative coolant to a blend containing 10-25 % of C 2 F 6 (hexafluoro-ethane). Such a change will reduce the evaporation temperature to assure thermal stability following radiation damage accumulated at full LHC luminosity.Central to this upgrade is a new ultrasonic instrument in which sound transit times are continuously measured in opposite directions in flowing gas at known temperature an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…A blend containing 20-25% C 2 F 6 in C 3 F 8 would enable a lower evaporation temperature for the same pressure, thus satisfying the system requirements. A series of tests has been performed over a range of C 2 F 6 /C 3 F 8 molar concentrations, using a test station that thermally reproduced an installed SCT cooling circuit (Bates et al 2013;2015;Rossi et al, 2014). Future studies of blend circulation in a thermosiphon are envisioned.…”
Section: Replacement Of the Present Compressor-driven Recirculator Wimentioning
confidence: 99%
“…A blend containing 20-25% C 2 F 6 in C 3 F 8 would enable a lower evaporation temperature for the same pressure, thus satisfying the system requirements. A series of tests has been performed over a range of C 2 F 6 /C 3 F 8 molar concentrations, using a test station that thermally reproduced an installed SCT cooling circuit (Bates et al 2013;2015;Rossi et al, 2014). Future studies of blend circulation in a thermosiphon are envisioned.…”
Section: Replacement Of the Present Compressor-driven Recirculator Wimentioning
confidence: 99%
“…It is installed in the cir cuit circulating the gas mixture to be analyzed and is designed to allow simultaneous on-line analysis and flowmetry through the transmission of sound pulses in opposite directions. In low flow applications the sound path is usually aligned with the gas flow direction [6], [7], while for high flows it crosses the gas flow at an angle, with transducers positioned so as to minimize turbulence and pressure drop in the flowing gas. Our studies have shown that high precision flow measurement is possible without the requirement of the entire sound path length being contained within the flowing gas volume.…”
Section: A the Mechanical Envelopementioning
confidence: 99%
“…Our studies have shown that high precision flow measurement is possible without the requirement of the entire sound path length being contained within the flowing gas volume. We have developed several instruments with angled and axial geometries [6].…”
Section: A the Mechanical Envelopementioning
confidence: 99%
See 2 more Smart Citations